INSTALLATION OF SOLAR PANELS FOR FILTRATION SYSTEMS ON KOI FISH CULTIVATION IN SUMBERINGIN KIDUL VILLAGE, TULUNGAGUNG REGENCY - Asrori, Asrori; Hadi Susilo, Sugeng; Hidayat, Mohammad Noor; Heryanto Eryk, Irwan; Maskur, Maskur (LPPM Univ. Ibn Khaldun Bogor, 2022)
The large electricity bill for aerators and filter pumps in Koi fish farming ponds is a problem for PPM (Community Service) partners. In addition, long-term power outages can cause fish death. This koi fish farming located in Tulungagung district has an area of ​​about 2000 m2 which is divided into several pond plots. The decline in the quality of Koi fish is also caused by poor filtration. The purpose of this activity is to install a micro-scale Solar power plant. This micro Solar Power Plant is used as a power source for filter pumps and pond aerators. The installed 600 Wp Solar Power Plant system consists of 4 solar panels with a capacity of 150 Wp each, an 850 VA hybrid inverter, and a 100 Ah VRLA battery. Electrical energy from Solar Power Plant can power a 75 W pump with a capacity of 26000 L/h. The installation of solar panels in this pool can produce an average of 2.5 kWh of electrical energy/day. So that the electricity savings from PLN can reach IDR. 108,352.5 per month.